2021
DOI: 10.1002/adom.202100245
|View full text |Cite
|
Sign up to set email alerts
|

Broadband, High‐Sensitivity Graphene Photodetector Based on Ferroelectric Polarization of Lithium Niobate

Abstract: 2D graphene has attracted extensive attention as a promising candidate for high‐performance photodetectors because of its superior optoelectronic properties. However, the realization of high‐sensitivity broadband graphene photodetectors remains a challenge. Lithium niobate (LiNbO3) has the advantages of spontaneous polarization, high dielectric constant, and high voltage electric coefficient, and it can improve the photoelectric detection characteristics of graphene by polarized doping. In this work, n‐ and p‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(31 citation statements)
references
References 84 publications
(143 reference statements)
1
29
0
1
Order By: Relevance
“…Meanwhile, the results showed that the band arrangement of layered heterostructures can be controlled by lattice engineering of 2D nanosheets to improve the photoelectric properties. Similarly, Guan et al showed that heterojunction formation by doping graphene could improve the light-detection capability of detections in their device based on ferroelectric polarization of L i NbO 3 [108]. The detectors' performance, such as detectivity and responsivity, improved by several orders of magnitude compared to previously reported devices.…”
mentioning
confidence: 86%
“…Meanwhile, the results showed that the band arrangement of layered heterostructures can be controlled by lattice engineering of 2D nanosheets to improve the photoelectric properties. Similarly, Guan et al showed that heterojunction formation by doping graphene could improve the light-detection capability of detections in their device based on ferroelectric polarization of L i NbO 3 [108]. The detectors' performance, such as detectivity and responsivity, improved by several orders of magnitude compared to previously reported devices.…”
mentioning
confidence: 86%
“…2, LN has a strong pyroelectric coefficient, which is suitable for the fabrication of a pyroelectric PD. 48,336 As the pyroelectrical current is inversely proportional to the dielectric thickness, 337 a thinner LN thickness is preferred in such devices. 338 However, in the typical bulk LN platform, it is challenging to reduce the LN thickness down to several micrometers, 339 whereas this will be quite easy when transferring this technology to the TFLN platform.…”
Section: Pyroelectric Devicesmentioning
confidence: 99%
“…More recently, Guan et al combined the pyroelectric effect of X-cut LN with graphene and realized a broadband (405 to 2000 nm) and high detectivity (∼8.65 × 10 14 Jones) graphene PD. 336 Compared with other pyroelectric material platforms, the high pyroelectrical coefficient feature of LN will continually get attention, especially for some applications such as gas sensing.…”
Section: Pyroelectric Devicesmentioning
confidence: 99%
“…[60] The graphene/carbon QD heterostructure photodetectors also show an ultrashort rise time of 0.93 µs and a fall time of 2.24 µs (Figure 3e,f), which is much faster than the response time of graphene photodetectors (in the level of s or ms). [61] With the strong response to UV light, SnSe 2 QDs have also been hybridized with graphene into graphene/SnSe 2 QD heterostructure photodetectors, [30] which shows an R of 7.5 × 10 3 AW −1 with a rise time of 0.31 s and a fall time of 1.3 s (corresponding to UV light, λ = 405 nm). Graphene/ZnO QD heterostructure photodetector shows a high R of 247 AW −1 (corresponding to UV, λ = 325 nm) with a response time of ms. [27] The introduction of graphene/QD heterostructures can also boost the performance of visible photodetectors.…”
Section: Significance Of Graphene/qd Heterostructuresmentioning
confidence: 99%